HRM Practices Across Different Cultures: an Evidence-Based Study in Germany and Ghana - Adinda Ayu Putri Sugiono; Sherissa Callista Huanggino; Rina Alfiyah Rahmah; Ely Farhana Nadya Nadra; Ainu Farhan Alhafi; Syarif Hidayatullah (International Journal of Social, Economic, and Business, 2024)
This research is a descriptive qualitative study that aims to describe cross-cultural human resource management (HRM) practices in Germany and Ghana. This research method uses literature studies from various sources such as journals and books related to cross-cultural HRM practices. The results of the discussion show that HRM practices in Germany involve the experience of transporting workers in a spatial labor context based on technological change, while in Ghana, the focus is on the consequences of permanent layoffs from the civil service. The implication of this research is the need for attention to the impact of poor work experience on one's employment, as well as the importance of re-employment programs for laid-off workers. In addition, the research also highlights the importance of a competency-based training discipline perspective in the acquisition of occupational skills, particularly in the field of OSH in Germany. These implications emphasize the need for cross-sectoral cooperation in addressing OHS challenges.